Analyzing Design Principles of Floor Plan of Hue Imperial Palaces, Vietnam - Le, An Vinh (Engineering Research: Perspectives on Recent Advances Vol. 5, 2025)
The Complex of Hue Monuments (abbreviated as the Monuments), the first UNESCO World Cultural Heritage site in Vietnam (UNESCO), is well-known for its wealth of scientific materials for research. This paper begins by providing a general introduction to the construction history and architectural typology of the Hue Imperial Palaces (abbreviated as the Imperial Palaces), a key component of the Monuments. These include the existing heritage buildings located within the Hue Citadel and the Emperor Mausoleums of the Nguyen dynasty (1802–1945). Next, this paper examines the floor plan design methods of the Imperial Palaces, with particular focus on the Twin-Ridge Beam Buildings (abbreviated as Twin Buildings), which are unique in ancient Asia. The name of this building type is derived from its characteristic design, which consists of two or three buildings connected and placed on the same platform. This construction style represents the highest level of architectural achievement during the Nguyen dynasty. Drawing mainly from historical documents of the Nguyen dynasty, surveys of remaining heritage Twin Buildings, dimensional analysis, investigations into traditional design methods, and interviews with master carpenters, the proportions of the floor plans were analyzed and the primary architectural design methods used were re-determined. Through this study, the units of measurement, parametric factors, design principles, and design processes for the floor plans of Twin Buildings have been clearly defined. In addition, this study provides a comprehensive understanding of the principles behind the floor plan design of the Twin Buildings in Hue imperial architecture. It also offers valuable guidance for the precise restoration and reconstruction of the Monuments. Moreover, the findings published in this paper serve as a valuable reference for researchers, graduate students, and architecture students, contributing to academic education and scientific research.